The "Shackleton Site" (IODP Site U1385) on the Iberian Margin - D. A. Hodell; L. Lourens; D. A. V. Stow; J. Hernández-Molina; C. A. Alvarez Zarikian; the Shackleton Site Project Members (Scientific Drilling, 2013)
Nick Shackleton's research on piston cores from the Iberian margin highlighted the importance of this region for providing high-fidelity records of millennial-scale climate variability, and for correlating climate events from the marine environment to polar ice cores and European terrestrial sequences. During the Integrated Ocean Drilling Program (IODP) Expedition 339, we sought to extend the Iberian margin sediment record by drilling with the D/V JOIDES Resolution. Five holes were cored at Site U1385 using the advanced piston corer (APC) system to a maximum depth of ~155.9 m below sea floor (m b.s.f.). Immediately after the expedition, cores from all holes were analyzed by core scanning X-ray fluorescence (XRF) at 1 cm spatial resolution. Ca/Ti data were used to accurately correlate from hole-to-hole and construct a composite spliced section, containing no gaps or disturbed intervals to 166.5 m composite depth (mcd). A low-resolution (20 cm sample spacing) oxygen isotope record confirms that Site U1385 contains a continuous record of hemipelagic sedimentation from the Holocene to 1.43 Ma (Marine Isotope Stage 46). The sediment profile at Site U1385 extends across the middle Pleistocene transition (MPT) with sedimentation rates averaging ~10 cm kyr−1. Strong precession cycles in colour and elemental XRF signals provide a powerful tool for developing an orbitally tuned reference timescale. Site U1385 is likely to become an important type section for marine–ice–terrestrial core correlations and the study of orbital- and millennial-scale climate variability.